A Scapegoat Model of Exchange Rate Fluctuations - Philippe Bacchetta; Eric van Wincoop (Swiss National Bank, Study Center Gerzensee, 2004)
While empirical evidence finds only a weak relationship between nominal exchange rates and macroeconomic fundamentals, forex markets participants often attribute exchange rate movements to a macroeconomic variable. The variables that matter, however, appear to change over time and some variable is typically taken as a scapegoat. For example, the current dollar weakness appears to be caused almost exclusively by the large current account deficit, while its previous strength was explained mainly by growth differentials. In this paper, we propose an explanation of this phenomenon in a simple monetary model of the exchange rate with noisy rational expectations, where investors have heterogeneous information on some structural parameter of the economy. In this context, there may be rational confusion about the true source of exchange rate fluctuations, so that if an unobservable variable affects the exchange rate, investors may attribute this movement to some current macroeconomic fundamental. We show that this effect applies only to variables with large imbalances. The model thus implies that the impact of macroeconomic variables on the exchange rate changes over time.
Keywords: 330; Wechselkurs; Theorie; Wirkungsanalyse